Alih Fungsi Lahan Gambut dan Cadangan Karbon di Kabupaten Pulang Pisau: Tinjauan Literatur dalam Perspektif Ekoteologi Islam - Miftah Az-Zura Salsabila; Nur Hasanah Nasution; Reva Rahmadani; Yola Nurlatifah; Adhi Munajar (Mataram University, 2026)
Peatland ecosystems represent the largest terrestrial reservoirs of organic carbon and possess exceptionally high ecological and climatological value. However, they are also among the most vulnerable ecosystems to land-use conversion pressures. This literature study aims to comprehensively examine how peatland conversion—including oil palm plantation expansion, agriculture, settlements, and drainage canal development—contributes to the decline of carbon stocks in Pulang Pisau Regency, Central Kalimantan, from the perspective of Islamic ecotheology. The study employed a Systematic Literature Review (SLR) method with thematic analysis of 25 scientific literature sources covering aspects of peatland physical and chemical degradation, CO₂ emission dynamics, peat fires, hydrological function decline, and Islamic theological values related to environmental management. The findings indicate that extensive peatland conversion accelerates the decomposition of organic matter, releases substantial carbon reserves into the atmosphere, and increases the frequency of peatland fires. Case studies from the Kahayan–Sebangau Peat Hydrological Unit, Kanamit Barat Village, and Taruna Jaya Village provide strong evidence that drainage development exceeding the natural recovery capacity of peatlands leads to severe ecological degradation and ultimately transforms peatlands into net carbon emission sources. On the other hand, mitigation approaches such as peat hydrological restoration, revegetation with native species, rewetting programs, and community-based peatland management have proven effective in reducing the rate of degradation. From the perspective of Islamic ecotheology, peatland degradation contradicts the principles of khalifah fil ardh (stewardship of the Earth), amanah (trust), mizan (balance), and the prohibition of fasad fil ardh (environmental destruction). This literature review concludes that safeguarding peatland ecosystems in Pulang Pisau Regency requires strengthening cross-sectoral regulations, implementing continuous ecological monitoring, and integrating Islamic values as a moral foundation in all peatland management policies within the region.